Production of corn in Serbia in the light of climate change - Latković, Dragana; Crnobarac, Jovan; Jaćimović, Goran; Visković, Jelena (Acta Agraria Debreceniensis, 2018)
This paper presents the basic elements of maize production technology in Serbia. For their good knowledge, it is necessary to be familiar with the basic biological requirements of the species, phenology and its particular requirements for water, heat, soil conditions and mineral nutrition. A special emphasis in this paper is given to recent research by the author regarding the correction of production technology (selection of hybrids, time and density of sowing, etc.) from the aspect of knowing the weather conditions of the year to the moment of sowing and the amount and position of available nitrogen in the soil profile during the spring before sowing. In the light of predicted climate change conditions for the Republic of Serbia, the authors of this paper have proposed and appropriated adaptation measures. The general conclusion is that there are no general recipes for the correct production technology of this plant species, but should be adapted to each specific year, field and hybrid.